Use of vincristine sulphate, subcutaneously, for the control of canine transmissible venereal tumour: a retrospective study of seven cases in Camagüey, Cuba - Peña G., Iván (2017)
The aim of this retrospective study was to show the use of vincristine sulfate via subcutaneous in the control of genital and extragenital Canine Transmissible Venereal Tumour (TVT), by reviewing seven cases treated between 2000 and 2016 with clinical signs compatible with TVT. The clinical diagnosis of TVT was based on the macroscopic morphology and location of tumours and the signs of this pathology. Chemotherapy with vincristine sulfate at doses of 0.025 mg/kg for 3 to 6 weeks was effective in all cases, with remission of clinical signs.